KAJIAN LITERATUR TENTANG PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI DAMPAK MEDIA SOSIAL TERHADAP AKHLAK REMAJA - 'Izzah, Yusriya Ni'matul; Putri, Aliyah Salsabila; Sandrika, Tutus; Ramadhani, Denissa Aulia; Ristamala, Zulfa Telian; Fairuz, Shofiyana Nadia (Kreatif: Jurnal Pemikiran Pendidikan Agama Islam, 2026)
The development of social media has had a major impact on teenagers, not only as a means of communication and entertainment, but also in character building. Social media provides opportunities to broaden one's horizons and social networks, but on the other hand, it raises moral issues, such as a decline in language ethics, neglect of worship and study, and the emergence of deviant behavior and a consumptive lifestyle. This study examines the role of Islamic Religious Education (IRE) in responding to these dynamics and formulating strategies for character building among adolescents. Using a qualitative approach based on literature review, the results show that IRE serves as a moral fortress and a means of character building. The recommended strategies include strengthening the curriculum with Islamic digital literacy, pedagogical innovation by teachers, family and school involvement, and the use of creative technologies such as Islamic applications, gamification, and virtual mentoring. With the integration of these strategies, PAI can function as an adaptive educational instrument that strengthens youth morals.